Disentangling the Effects of Matching Content and Simultaneous Speech on Phonetic Adaptation. Issue 1 (3rd April 2022) - Rombout, Lisa E.; Postma-Nilsenová, Marie
ABSTRACT: Past studies demonstrated that interlocutors mutually affect each other's vocal behavior in joint speech situations. However, findings on exactly how and when these adaptive processes occur are inconsistent. We propose a novel experimental paradigm, the 'One-Voice Professor' game, that explicitly separates content matching ("saying the same thing") from simultaneity ("speaking at the same time"), in an effort to systematically investigate different joint speech conditions. In our first experiment, we analyzed the vocal characteristics of 96 participants who engaged in joint speech with a recorded voice, in a 2-by-2 experimental design. Results indicate significant effects on the fundamental vocal frequency (f0), with the strongest f0 adaptation in the alternating-and-matching condition, and f0 divergence in the simultaneous-and-matching condition. Since these effects could have been impacted by the fact that speakers could not mutually adapt with the recorded voice, we applied the same paradigm in our second experiment to an interactive joint speech situation. Same-gendered dyads (n = 66) improvised speech together in interviews designed to separate matching from simultaneity. The results show main effects of the conditions, with matching leading to stronger f0 adaptation and simultaneity to divergence on secondary voice characteristics (f1, f2, and harmonics-to-noise ratio (HNR)). These findings confirm the hypothesis that simultaneity and matching of speech influence phonetic adaptation differently.